2012
DOI: 10.5539/jgg.v4n4p40
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Analysis of Land Use/Cover Change of Lokoja - A Confluence Town

Abstract: Land use/land cover information is essential for a number of planning and management activities. The general patterns of land use/cover as they were recorded in remotely sensed data were discussed in this study. Multi-date satellite imageries (Landsat TM 1986, Landsat ETM+ 2001, Landsat ETM+ 2006 of 30m spatial resolution respectively and SPOT 5, 2007 of 10m spatial resolution) were obtained and used for the study. These images were enhanced, resampled, georeferenced and classified for the assessment of spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…(Adeoye, 2012). In a study of land use / land cover change in Lokoja, Adeoye (2012) reported that natural environment particularly vegetation, wetland resources, water bodies and mountain terrain were threatened as they were reducing gradually in the area extent over time, while the built up area expand massively. The built up area of Lokoja is located at the eastern part of River Niger, while the Mount Patti is located at the western part of the city (figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…(Adeoye, 2012). In a study of land use / land cover change in Lokoja, Adeoye (2012) reported that natural environment particularly vegetation, wetland resources, water bodies and mountain terrain were threatened as they were reducing gradually in the area extent over time, while the built up area expand massively. The built up area of Lokoja is located at the eastern part of River Niger, while the Mount Patti is located at the western part of the city (figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…Low rainfall reduces the area and volume of water in ephemeral ponds and subsequently, the longevity of the ponds. Adeoye [ 19 ] attributed reduction in wetland area to climatic variability. Abundant rainfall contributes to rapid growth of vegetation and this would spread to other areas that are devoid of vegetation, which could be the case with the observed 64% increase in woody vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted within Lokoja metropolis, along the length of the Niger and Benue River Basin. The town is geographically located between latitude 7° 45' 27.56'' -7° 51' 04.34'' N and longitude 6°41' 55.64'' -6°45' 36.58'' E of the equator (Adeoye, 2012). The annual rainfall pattern is 1150mm.…”
Section: Materials and Methods Study Areamentioning
confidence: 99%